PENINGKATAN KEMAMPUAN BERBICARA ANAK MELALUI VIDEO ANIMASI DI TAMAN KANAK-KANAK NEGERI MODEL ARGAMAKMUR BENGKULU UTARA - Widiawati Debora Tarigan; Indra Yeni (STKIP Subang, 2026)
This study aims to improve children's speaking skills through animated videos at the Argamakmur Model State Kindergarten, North Bengkulu, with the research subjects being 10 children in group A aged 4-5 years, in the 2025-2026 academic year. In this classroom action research, the researcher used the Kurt Lewin model of CAR, Kurt Lewin developed an operations research model for a system consisting of input, transformation, and output subsystems, the initial problems faced by individuals or groups of children were diagnosed, (Arif & Oktaviana, 2023). Classroom action research has been carried out by researchers in two cycles, each cycle the researcher conducted three meetings, each cycle consisted of 4 components that must appear in the series of classroom action research, namely planning, action, observation, and reflection, (Purnama, et al., 2020). The data collection techniques used by researchers were observation, interviews, and documentation, (Sridadi et al., 2026). The data analysis techniques used were descriptive qualitative and quantitative. Qualitative data were obtained from observations and reflections, while quantitative data were calculated as percentages to determine the increase in student activity in each cycle (Sridadi, 2026). From the overall results of observations, interviews, and documentation, it was found that 60% of children had not completed the initial observation, 30% had not completed the end of cycle I, and 10% had not completed the end of cycle II. The use of animated video media has been proven to improve children's speaking skills during the CAR process by 30% at the Argamakmur Model State Kindergarten, North Bengkulu.